2012
DOI: 10.3109/02699206.2011.636499
|View full text |Cite
|
Sign up to set email alerts
|

Early vocalization of preterm infants with extremely low birth weight (ELBW), part I: from birth to expansion stage

Abstract: The vocalization of preterm infants with extremely low birth weight (ELBW) up to the expansion stage was systematically described and compared with those of healthy full-term infants. The sample consisted of 18 preterm ELBW infants and the control group of 11 full-term infants. The follow-up was performed intensively using video-recordings. The vocalization of the preterm and full-term infants was analyzed quantitatively according to the categorical stages created by Oller. A descriptive analysis of all the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…In the present study, as well as in our earlier study (Törölä, Lehtihalmes, Heikkinen, et al, 2011), both the preterm and full-term infants failed to produce some skills at each developmental stage. Infants with repeated airway and middle ear infections during the data collection period were those who especially failed to produce syllable types and combinations in both the preterm and full-term groups.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…In the present study, as well as in our earlier study (Törölä, Lehtihalmes, Heikkinen, et al, 2011), both the preterm and full-term infants failed to produce some skills at each developmental stage. Infants with repeated airway and middle ear infections during the data collection period were those who especially failed to produce syllable types and combinations in both the preterm and full-term groups.…”
Section: Discussioncontrasting
confidence: 49%
“…The number of vocalizations in the preterm infants was smaller and the increase in vocalization was slower than that in the full-term infants throughout the babbling period up to the first word. In our earlier study (Törölä, Lehtihalmes, Heikkinen, et al, 2011), a poorer repertoire of preverbal vocalization was observed in the preterm infants than in the full-term infants. Oller et al (1994) suggested that preterm infants present mature vocal patterns less consistently during the first year than the full-term infants, a tendency which was also observed in the present study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Low volubility was indeed observed in infants with autism (Patten et al, 2014). A reduction in volubility also was reported for premature infants at some points in their development (Törölä, Lehtihalmes, Hikkinen, Olsén, and Yliherva, 2012a, 2012b) although other investigations on premature infants have not observed this reduction (Oller et al, 1994). In addition, Berger and Cunningham (1983) showed strong volubility differences between typically developing infants and infants with Down syndrome but not always in the direction of low volubility for infants with Down syndrome.…”
Section: Introductionmentioning
confidence: 75%